2012
DOI: 10.1177/1352458512469697
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics of familial and sporadic multiple sclerosis patients

Abstract: While familial MS was associated with more severe T1-lesion volume and its MTR characteristics, there were no clinical status differences between familial and sporadic MS patients. Therefore, a better understanding of the genetic and/or epigenetic influences causing these differences can advance the understanding and management of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Family members were classified into first-, second-, and third-degree relatives as described previously. 10 There were 47 subjects in sporadic and 21 subjects in familial HC subgroups. Both subgroups were merged into 1 group composed of healthy relatives of patients with MS.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members were classified into first-, second-, and third-degree relatives as described previously. 10 There were 47 subjects in sporadic and 21 subjects in familial HC subgroups. Both subgroups were merged into 1 group composed of healthy relatives of patients with MS.…”
Section: Subjectsmentioning
confidence: 99%
“…8 However, other studies did not show clinical differences among familial and non-familial healthy control subject (non-fMS) forms. 2,9 Nevertheless, MR imaging studies by use of nonconventional techniques showed MR imaging differences between familial and non-familial MS. [10][11][12] In 2009, Okuda et al 13 introduced the term "radiologically isolated syndrome" (RIS) to describe subjects who show incidental brain MR imaging WM lesions suggestive of MS and who fulfill Barkhof criteria for dissemination in space (DIS) 14 but have no signs or symptoms of the disease. Overall, the prevalence of RIS is, according to postmortem studies, in a range of 0.06 -0.7%, with an age range of 16 -70.…”
mentioning
confidence: 99%
“…Patients with non-vascular etiology of WM lesions like MS can have heterogeneous presentations, which might partially reflect the variety of the clinical disease course and the evolution. While familial MS was associated with more severe T1-lesion volume, there were no clinical status differences between family and sporadic MS patients (66). Whereas, genetic factors can make familial MS patients more inclined to develop the disease than sporadic patients, other factors such as the environmental influence and the subjective (genetic) differences in response to injury seem to be critical for developing a diffuse and perhaps clinically significant development-relevant pathology in MS. Biologic confounders could influence the analysis of GM volumes, including the introduction of disease-modifying therapies, physiologic factors, normal aging, comorbidities, and daily fluctuations in brain volumes (67).…”
Section: Figure 4 | (A)mentioning
confidence: 82%
“…They demonstrated that familial MS is correlated with more severe T1-lesion volume and its MTR characteristics. Moreover, no clinical differences were found between the two groups of MS patients [ 37 ]. Growing number of new MS cases among family members in future has been reported and there are variations in the clinical path and survival between the genders of intermittent and familial cases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%